Caused motion events in Modern Uyghur: a typological perspective - Tusun Alimujiang; Hendriks Henriëtte (Linguistics)
Talmy’s motion event typology (Talmy, Leonard. 2000. Towards a cognitive semantics: Conceptual structuring systems, vol. 2. Cambridge, MA: The MIT Press) has served as an influential framework for exploring event representation across languages. While confirming its basic premises, many studies argued that the typology cannot fully capture the vast intra- and inter-typological variations. Consequently, proposals have been made to expand the typology and/or reconceptualize it as a typology of constructional strategies for encoding events. This article furthers this line of inquiry by examining caused-motion expressions by adult speakers of an understudied Turkic language, Modern Uyghur. Systematic analyses of lexicalization patterns, that is, which components are typically selected for expression, how frequently they are selected, and how they are packaged in syntactic constructions, show that Uyghur is a prototypical verb-framed language. It differs most strikingly from English (considered satellite-framed) in terms of lexicalization patterns. Detailed comparisons with French and Turkish (putatively verb-framed) reveal intra-typological variations in that Uyghur speakers systematically used verb-framed constructions while French and Turkish speakers exhibit much flexibility and a general preference for satellite-framed constructions. Overall, our data lend support to Talmy’s typology conceived as a strategy-based typological framework.